142k views
2 votes
If f(x) = -4x^2 - 6x - 1 and g(x) = -x^2 - 5x + 3, find (f + g)(x).

If f(x) = -4x^2 - 6x - 1 and g(x) = -x^2 - 5x + 3, find (f + g)(x).-example-1
User Cheyne
by
4.8k points

2 Answers

2 votes

B

note that (f + g)(x) = f(x) + g(x)

f(x) + g(x) = -4x² - 6x - 1 - x² - 5x + 3 ( collect like terms )

= - 5x² - 11x + 2


User Yuralife
by
4.7k points
3 votes

Answer:

The correct option is B.

Explanation:

The given functions are


f(x)=-4x^2-6x-1


g(x)=-x^2-5x+3

Using the p addition property of functions (f + g)(x) can be written as


(f+g)(x)=f(x)+g(x)

Substitute the values of each function in the above equation.


(f+g)(x)=-4x^2-6x-1-x^2-5x+3

Combine like terms.


(f+g)(x)=(-4x^2-x^2)+(-6x-5x)+(-1+2)


(f+g)(x)=-5x^2-11x+2

Therefore the correct option is B.

User Izb
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.